Analisis Sentimen Pengaruh Operasi Zebra terhadap Citra Polri di Mata Masyarakat pada brand24: Studi Respons Publik dan Kepatuhan Berkendara - Nabila Juannita Enas; Rina Tisna Nurasih; Dwi Novaria Misidawati (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study discusses how the public responds to Operation Zebra and how this response affects the image of the Indonesian National Police (Polri). In this digital age, public opinion is often expressed through social media and online news, so this study uses Brand24 to monitor online conversations and public sentiment. Data was collected during the period of November–December 2025 using keywords related to Operation Zebra and traffic law enforcement activities. The results of the study show that Operation Zebra was a topic that was widely discussed by the public. Positive sentiment was more prevalent, especially among people who believed that this operation helped improve order and safety on the roads. However, negative sentiment still existed, usually related to experiences that were considered unfair or unclear procedures during raids. The majority of conversations originated from social media and news portals, indicating that public opinion is shaped by a combination of direct experiences and media coverage. Overall, the findings of this study show that Operation Zebra contributes significantly to the positive image of the Indonesian National Police, although public criticism still needs to be addressed. Monitoring digital sentiment in this manner can serve as a basis for evaluation for the Indonesian National Police in improving transparency, service, and public communication in the future.